Constructing Political Reality in International Crisis: Media Framing of Donald Trump’s 48-Hour Ultimatum on the Iran-US/Israel Conflict - Siti Komala Mutiara; Muhammad Armahadi Rahmawan; Ferinica Innestesya; Anjas Aditya Hartono; Malik Ibrahim (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze the social construction of political reality regarding the Iran–United States/Israel triadic conflict in Indonesian online journalism, specifically examining how media framing of Donald Trump’s 48-hour ultimatum shapes public risk perception and global moral accountability. Methodology: This study employs a descriptive-interpretive qualitative design utilizing Robert N. Entman’s framing analysis model. The data sources comprise representative news articles harvested from diverse Indonesian digital news platforms, including state-owned, market-driven, and independent networks. Data were systematically collected through non-participant observation and purposive digital screening, followed by text categorization based on Entman’s four diagnostic functions: problem definition, causal diagnosis, moral judgment, and treatment recommendation. Main Findings: The findings indicate that Indonesian online media generally transformed the military ultimatum into a broader social reality of global economic crisis centered on the Strait of Hormuz. Ideological variations significantly dictated the framing: market-driven platforms simplified crisis causality by placing explicit blame on Iran to amplify economic anxieties, whereas state-owned and independent media maintained institutional neutrality by balancing multi-actor political justifications. These structural variations confirm that media acts as an ideological apparatus that packages moral judgments, heavily governing public empathy and civic consciousness toward foreign crises. Novelty/Originality of this study: This study contributes to communication sociology and social science by shifting from static bilateral conflict analysis to a multi-actor geopolitical triad during an acute escalation point. It uncovers the institutional maneuvering of media in a major Muslim-majority nation trapped between global economic dependencies, Islamic solidarity, and diplomatic neutrality, providing a crucial conceptual template for how reality is constructed under crisis-driven temporal constraints.